STUDI KONDISI PANGKALAN PENDARATAN IKAN (PPI) BATULICIN DI KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Nani Jayusman; Iriansyah Iriansyah; Irhamsyah Irhamsyah (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2017)
The aims of this study were: (1) find out main, functional, and supporting facility. (2) The facilities in Fishing Port Batulicin. (3) Factor of power, weakness, opportunity and threat for Fishing Port Batulicin. Data collection is a direct observation, interview and direct measurement.The data analyzed through descriptive analysis and SWOT analysis. The results were: (1) The main facilities consist of ground, quay, jetty, pool, sheet file, asphalt complex road, concrete complex road, parking lot and drainage; the functional facilities consist of TPI, center building of fish marketing and distribution, factories, concrete fence, cold storage, ABF, guardhouse, SPBN,electricity from PLN, generator set, house generator set, water tower, water tank, UPSA office,police station and dump; supporting facilities are little shops, guardhouse, public toilet and bathroom (MCK), staff house, medical clinic, meeting hall, forklift, water pump, big basket, smallbasket, basket with capacity 40 kg, basket with capacity 50 kg, ice crusher, hanging scales and tablescales, sprayer machine, water tank, cool box fiber, cool box plastic, hold of a ship, cart,megaphone, electrical water pump, and whiteboard. (2) The condition of main facilities: 77% are ingood condition, 11,1% are slightly damaged, and 11,1% are seriously damaged; functional facilities: 68% are in good condition, 18,75% are slightly damaged, and 12,5 % are seriously damaged; supporting facilities: 55,39% are in good condition, 3,36% are slightly damaged, and41,25 % are seriously damaged. (3) The powers are the ground was not used optimally yet, the amount of fish production in Fishing Port Batulicin tends to increase, the area of Fishing PortBatulicin is strategic, the facilities and infrastructures can be easily accessed, the facilities owned by Fishing Port Batulicin are convenient with Regulation of the Minister of Marine Affairs andFisheries 2012 about Fishery Port along with the location of local market near Fishing PortBatulicin. The weaknesses are: the facilities in Fishing Port Batulicin are less maintained and damaged, the lack of fishery expert, the ships that lean in Fishing Port Batulicin are mostly onlyvisitor, lack of awareness of hygiene, and fishing ground is far from Fishing Port Batulicin. Theopportunities are to build functional facilities like dock and workshop, increa the PAD and createjob fields for people around the harbor. The threats are some facilities in Fishing Port are damaged,illegal fishing, and harbor area that is not used yet( if the condition is left continuously, it is going to experience the abrasion).